Cover Image, Volume 38, Issue 9. Issue 9 (17th August 2017) - Xu, Qifang; Tang, Qingling; Katsonis, Panagiotis; Lichtarge, Olivier; Jones, David; Bovo, Samuele; Babbi, Giulia; Martelli, Pier L.; Casadio, Rita; Lee, Gyu Rie; Seok, Chaok; Fenton, Aron W.; et al.
Abstract : On the cover : This cover image, by Qifang Xu et al., is based on the Special Article Benchmarking predictions of allostery in liver pyruvate kinase in CAGI4, Pages 1123–1131. DOI: 10.1002/humu.23222 .